Evaluation of Antioxidant Activity of Methanol Extract of Neem Leaves (Azadirachta indica) Using DPPH, ABTS, and FRAP Methods - Noer Aini; Andri Tilaqza (CV. AKBAR PUTRA MANDIRI, 2025)
Introduction: Azadirachta indica leaves are rich in bioactive compounds with antioxidant potential. Aims: To assess the antioxidant activity of methanolic neem leaf extract using three in vitro methods DPPH, ABTS, and FRAP and to identify its major secondary metabolites. Method: Extraction was performed using Ultrasound-Assisted Extraction (UAE) with methanol as the solvent. Qualitative phytochemical screening was conducted to determine the presence of key antioxidant-related compounds. Antioxidant activity was evaluated using a microplate reader, and IC₅₀ values were calculated based on the inhibition percentage across several concentrations. Results: Phytochemical analysis confirmed the presence of flavonoids, phenolics, terpenoids, and alkaloids. The extract showed strong antioxidant activity in the DPPH assay, with an IC₅₀ value of 54.91 ppm. However, the ABTS and FRAP assays did not yield measurable IC₅₀ or RP₅₀ values, even at concentrations up to 1000 ppm, suggesting limited electron transfer-based antioxidant capacity. These results indicate that the extract’s primary antioxidant mechanism is likely through hydrogen atom transfer (HAT), rather than single electron transfer (SET). Conclusion Methanolic extract of A. indica leaves exhibits strong free radical scavenging activity through the HAT mechanism, as shown in the DPPH assay. This activity is presumably due to the presence of flavonoids and phenolics.